Plasmablastic plasmacytoma of the rectum and anal canal in a patient with ulcerative colitis - Jankovic, Katarina; Rajic, Sanja; Dragasevic, Sanja; Jovanovic, Ivan (Gastroenterology Review/Przegląd Gastroenterologiczny, 2021)
Plasma cell neoplasms (PCN) represents a group of tumours originating from abnormal plasma cells, which are further classified into multiple myeloma (MM), medullary plasmacytoma (MP), and extramedullary plasmacytoma (EMP) [1, 2]. Extramedullary plasmacytoma is a rare entity and usually involves the nasopharynx or upper respiratory tract [3]. Involvement of the gastrointestinal tract (GIT) occurs in approximately 10% of EMP cases, with the stomach and small intestine being most commonly involved [1, 3–5]. Solitary EMP of the rectum is exceedingly rare [3].